Chemical characterization, bioactive compounds, antioxidant activity and rheological behavior of stingless bee honey collected in the state of Bahia (Research, Society and Development, 2024)
The present study was developed with the aim of evaluating and determining the physicochemical characteristics, the content of bioactive compounds, the antioxidant activity and the rheological behavior of samples of honey from stingless bees, collected in the State of Bahia, three of the samples being from the species Melipona quadrifasciata (Mandaçaia), one Tetragonisca angustula (Jataí) and one from Melipona scutellaris (Uruçu nordestina). The results of the physical-chemical analyses obtained were a variation of 3.08 to 4.36 for pH, 17.52 to 132.22 meq.kg-¹ for acidity, 64.08 to 80.42% for total soluble solids, 53.97 to 66.69% for reducing sugars, 1.41 to 13.82% for apparent sucrose, 17.80 to 34.13% for moisture, 0.31 to 3.16% for ash, as well as values ​​of 12.05 to 26.52 mg.kg-¹ for hydroxymethylfurfural among the five honey samples. Regarding the bioactive compounds, levels of 9.90 to 24.20 mg EAG.100g-¹ were found for total phenolic compounds, 5.80 to 14.20 mg.100g-¹ for total chlorophyll, 0.03 to 0.20 mg.100g-¹ for total anthocyanins, 0.11 to 0.23 mg.100g-¹ for yellow flavonoids and 3.64 to 6.75 mg.100g-¹ for vitamin C. The honeys presented antioxidant capacity of 17.50 to 62.64%. In the rheological analysis, a Newtonian fluid behavior with constant viscosity was observed for all the samples studied. Therefore, more research is needed to investigate the properties of honey from stingless bees in different biomes and national legislation that addresses the quality parameters of honey from meliponines, respecting their particularities, since the parameters established by national bodies and institutions refer only to honey from Apis melífera.